Baker's Cyst Filled with Hematoma at the Lower Calf - Yoo, Moon-Jib (Knee Surg Relat Res, 2014)
Baker's cyst is a distension of the gastrocnemius-semimembranosus bursa of the knee, which communicates with the posterior portion of the joint capsule. Baker's cyst is commonly located in the inferomedial or superficial layers of the knee joint and rarely extends laterally or proximally. Complications of Baker's cysts are dissection, rupture, pseudothrombophlebitis, leg ischemia, nerve entrapment, and compartment syndrome. However, hematomas in the Baker's cyst have not been reported in Korea. We report a rare case of hematoma in the Baker's cyst with subfascial extension into the calf. The hematoma was demonstrated by magnetic resonance imaging and removed by mass excision.